Identification and characterization of trans-3-hydroxy-l-proline dehydratase and Δ(1)-pyrroline-2-carboxylate reductase involved in trans-3-hydroxy-l-proline metabolism of bacteria - Watanabe, Seiya (Elsevier, 2014)
trans-4-Hydroxy-l-proline (T4LHyp) and trans-3-hydroxy-l-proline (T3LHyp) occur mainly in collagen. A few bacteria can convert T4LHyp to α-ketoglutarate, and we previously revealed a hypothetical pathway consisting of four enzymes at the molecular level (J Biol Chem (2007) 282, 6685–6695; J Biol Chem (2012) 287, 32674–32688). Here, we first found that Azospirillum brasilense has the ability to grow not only on T4LHyp but also T3LHyp as a sole carbon source. In A. brasilense cells, T3LHyp dehydratase and NAD(P)H-dependent Δ(1)-pyrroline-2-carboxylate (Pyr2C) reductase activities were induced by T3LHyp (and d-proline and d-lysine) but not T4LHyp, and no effect of T3LHyp was observed on the expression of T4LHyp metabolizing enzymes: a hypothetical pathway of T3LHyp → Pyr2C → l-proline was proposed. Bacterial T3LHyp dehydratase, encoded to LhpH gene, was homologous with the mammalian enzyme. On the other hand, Pyr2C reductase encoded to LhpI gene was a novel member of ornithine cyclodeaminase/μ-crystallin superfamily, differing from known bacterial protein. Furthermore, the LhpI enzymes of A. brasilense and another bacterium showed several different properties, including substrate and coenzyme specificities. T3LHyp was converted to proline by the purified LhpH and LhpI proteins. Furthermore, disruption of LhpI gene from A. brasilense led to loss of growth on T3LHyp, d-proline and d-lysine, indicating that this gene has dual metabolic functions as a reductase for Pyr2C and Δ(1)-piperidine-2-carboxylate in these pathways, and that the T3LHyp pathway is not linked to T4LHyp and l-proline metabolism.